Comparação da prevalência de exames coprológicos, testes sorológicos e exames hematológicos e a associação entre a resposta imunológica por Th1, Th2 e Treg em idosos na região metropolitana de João Pessoa - Paraíba - Sarmento, Ronaldo Rodrigues (2014)
Introduction and Objectives: This study highlights the importance of identifying the prevalence of intestinal parasites, compared with the seroprevalence of IgG antibodies to Entamoeba histolytica and Schistosoma mansoni, the research for antigens of Giardia lamblia in stool and with changes in blood count parameters, associating and describing the response Th1, Th2 and Treg in elderly of metropolitan area of João Pessoa, Paraíba. Methods: Quantitative cross-sectional study, with analysis of blood and stool samples collected from elderly in 2013 and 2014 years. To obtain the data, it was opted for the use of socioeconomic questionnaire. It was performed: cell culture of whole blood of patients; tests for detection of intestinal parasites in stool (different parasitological techniques); complete blood counts; serological survey for intestinal parasites in serum and antigen in the stool; dosage of culture supernatants to evaluate Th1, Th2 and Treg responses in elderly. Results: The detection rate of the intestinal parasites was 95% (115/121). It was observed a significantly higher prevalence of intestinal parasites in the elderly with low levels of education. In positive samples, it was observed a predominance of protozoa of amoebae group, intestinal parasites among several different genera and species. Results of serologic evaluation revealed a prevalence of 55% for Schistosoma mansoni and 34% for Entamoeba histolytica in blood; and 5.9% of Giardia lamblia in feces. The complete blood counts test demonstrated significant changes in the number of typical and atypical lymphocytes and in red blood cell count. It was analyzed and described Th1, Th2 and Treg responses, and significant changes in immune responses of the types of Th2 and Treg were observed. Conclusions: It was observed a very high prevalence of intestinal parasites, a predominance of intestinal protozoa and in several stool samples more than one parasite was detected. Low levels of education were associated with a higher prevalence of intestinal parasitosis in the elderly of João Pessoa-PB. The seroprevalence of Schistosoma mansoni was high in elderly, may be chronically ill. A high prevalence of Entamoeba histolytica was also observed in serum and feces of patients. A low prevalence of Giardia lamblia was observed. There was a moderate association of the results of the tests for detection of Giardia lamblia in the serum and feces. The changes in complete blood counts decreased number of red blood cells, can develop a probable indicates anemia in elderly and was found a deficiency in the production of lymphocytes T and B (typical and atypical ) lymphocytes . Probably due to immunosenescence, the elderly were unable to produce nitric oxide, responsible for the oxidative production of immune response; plus the inability to produce Th1 response and increased of immune responses of the types of Th2 and Treg.